Answer: x = 5
Explanation:
The given system of linear simultaneous equations is expressed as
y = - 6x + 33- - - - - - - - - - - - - - - - -1
y = 6x - 27- - - - - - - - - - - - - - - - -2
We would apply the method of substitution by substituting equation 2 into equation 1. It becomes
6x - 27 = - 6x + 33
Adding 6x to the left hand side and the right hand side of the equation, it becomes
6x + 6x - 27 = - 6x + 6x + 33
12x - 27 = 33
Adding 27 to the left hand side and the right hand side of the equation, it becomes
12x - 27 + 27 = 33 + 27
12x = 60
Dividing the left hand side and the right hand side of the equation by 12, it becomes
12x/12 = 60/12
x = 5